Legacies of Kanjogera: women political elites and the transgression of gender norms in Rwanda. Issue 1 (2nd January 2020) - Watkins, Sarah E.; Jessee, Erin
ABSTRACT: Kanjogera looms large in Rwandan history as a Queen Mother (1895–1931) – a position equal to that of the king – who wielded extraordinary political power. While she was not the first Rwandan woman to exercise this kind of power, she is arguably the most widely remembered in Rwandan popular culture largely due to the brutalities she allegedly inflicted upon her perceived enemies. But why do Kanjogera's violent excesses stand out when other monarchical figures also occasionally used violence to maintain or expand their power? What might the way her name is invoked in the present tell us about modern Rwandan gender norms and people's attitudes toward women who exercise significant political power? We respond to these questions by examining the permissible behaviours of Rwandan women political elites in historical perspective. Following an overview of Kanjogera's political legacy, we turn our attention to two First Ladies, Agathe Kanziga (1973–1994) and Jeannette Kagame (2000-present) who, for different reasons, are occasionally referred to as modern incarnations of Kanjogera. In these two cases, we argue Kanjogera's name serves as a rhetorical device that reveals ongoing anxieties about women exercising significant political power, while simultaneously undermining the politically prominent men with whom they are associated.